The Little Green Box of BRIGHT and EARLY Board Books : By Dr. Seuss - Seuss Dr. (New York : Random House, 1996)
Beginner's text of all sorts of silly rhyming words
On board pages
Keywords: Vocabulary -- Juvenile fiction